Cold treatment enhances low‐temperature flight performance in false codling moth, Thaumatotibia leucotreta (Lepidoptera: Tortricidae). (21st February 2019) - Boersma, Nevill; Boardman, Leigh; Gilbert, Martin; Terblanche, John S.
Abstract: In sterile insect technique programmes, temperatures experienced by insects during rearing and handling, along with cool temperatures after release, can negatively affect performance and activity levels. Phenotypic plasticity (trait modifications caused by prior stress exposure) can offset these effects but is poorly understood in many species and traits. We investigated the effects of a cold treatment (2 °C for 16 h) on flight performance in adult false codling moth, Thaumatotibia leucotreta . Using diverse methods, flight performance was tested using flight assays in the laboratory and in the field under varying environmental conditions. The flight performance of T. leucotreta in the laboratory was affected by cold treatment (relative to a 25 °C control group), test temperature and their interaction. Field recapture of released moths was significantly affected by the interaction between cold treatment and environmental conditions. Field recapture counts depended on the ambient temperature upon release. For example, under warmer conditions (>17 °C), the recapture count of cold‐treated moths was lower than that of the untreated control group, whereas the recapture count of cold‐treated moths at cooler temperatures was significantly higher. Our results suggest a temperature‐dependent interaction between acute cold exposure and flight performance in adult T. leucotreta, which may be used to enhance the efficacy of the sterile insect technique under cooler environmental conditions.